2023
DOI: 10.1111/ctr.14922
|View full text |Cite
|
Sign up to set email alerts
|

Sweet and simple as syrup: A review and guidance for use of novel antihyperglycemic agents for post‐transplant diabetes mellitus and type 2 diabetes mellitus after kidney transplantation

Abstract: Uncontrolled type 2 diabetes mellitus (T2DM) and post-transplant diabetes mellitus (PTDM) increase morbidity and mortality after kidney transplantation. Conventional strategies for diabetes management in this population include metformin, sulfonylureas, meglitinides and insulin. Limitations with these agents, as well as promising new antihyperglycemic agents, create a need and opportunity to explore additional options for transplant diabetes pharmacotherapy. Novel agents including sodium glucose co-transporter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 110 publications
1
4
0
Order By: Relevance
“…In this study, 46 % of the patients had PTDM/NODAT, which means that they were diagnosed with diabetes after transplantation. This finding is consistent with other studies that reported that 30–50 % of patients with renal transplants develop PTDM [19] , [20] , [21] . The high PTDM prevalence is linked to classic T2DM risk factors, such as older age and obesity, which are common among renal transplant recipients.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, 46 % of the patients had PTDM/NODAT, which means that they were diagnosed with diabetes after transplantation. This finding is consistent with other studies that reported that 30–50 % of patients with renal transplants develop PTDM [19] , [20] , [21] . The high PTDM prevalence is linked to classic T2DM risk factors, such as older age and obesity, which are common among renal transplant recipients.…”
Section: Discussionsupporting
confidence: 93%
“…Novel agents, including sodium glucose co-transporter 2 inhibitors (SGLT2i), glucagon-like peptide-1 receptor agonists (GLP1RA), and dipeptidyl peptidase IV inhibitors (DPP4i), show great promise for type 2 diabetes management in the non-transplant population. However, current experience with novel antihyperglycemic agents is primarily limited to single-center retrospective studies and case series [36].…”
Section: Post-transplant Diabetes Mellitus (Ptdm)mentioning
confidence: 99%
“…Based on these premises, the use of available drugs will be personalized for each patient in order to achieve the maximum benefit attributed to each drug while minimizing the associated adverse effects. In the case of the use of SGLT2i, it is recommended that concomitant treatment be modified, and that monitoring measures are implemented to optimize patient status and minimize potential adverse effects Adapted of [ 22 , 112 , 113 ].…”
Section: Figurementioning
confidence: 99%